Herakles on an Intaglio Seal Found at Phu Khao Thong in the Upper Thai-Malay Peninsula - Borell, Brigitte (Zeitschrift für Archäologie Außereuropäischer Kulturen, 2023)
The paper explores the iconographic scheme of a Herakles image engraved on an agate sealstone found at the archaeological site of Phu Khao Thong in southern Thailand. Although a number of Roman engraved gems have been found at sites in southern Thailand, in particular at sites in the region of the Isthmus of Kra including Phu Khao Thong, this seal is not a Mediterranean import of the Roman period. The iconographic and stylistic type of Herakles on the Phu Khao Thong seal fi nds its parallels among seals from the South Asian North and North-West. These Herakles images on locally produced seals are developed from Hellenistic Herakles types that occur already in the coinage of the Greek kings in Bactria and northern India. The article will be available as a PDF in the near future.